Differentiating Maternal Angiogenesis Factors between Early and Late Onset Preeclampsia: Higher sflt-1 in Early Onset Preeclampsia, Lower PlGF and Higher sflt-1/PlGF Ratio in Late Onset Preeclampsia - Serudji, Joserizal; Basyir, Vaulinne; Fadhillah, Tara (Cell and BioPharmaceutical Institute, 2024)
Background: Early onset preeclampsia (PE) is considered a fetal disorder that is associated with placental dysfunction. While late onset preeclampsia is considered a maternal disorder that associated with a normal placenta. An imbalance of angiogenesis factors, namely soluble Fms-like tyrosine kinase 1 (sFlt-1) and placental growth factor (PlGF) is not only a strong predictor of PE but can also be a predictor of poor outcomes or adverse complications of PE. This study was conducted to analyze the difference between angiogenesis factor sFlt-1 and PlGF in maternal serum between patients with early and late onset PE. Material and Methods: This was a cross-sectional study involving pregnant women with PE who were ≥18 years old and gestational age >20 weeks had singleton pregnancies. Subjects who had a major morphological abnormality of a fetus diagnosed with USG and chromosomal abnormality of the fetus were be excluded. Systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were measured using a digital blood pressure measuring instrument. sFlt-1 and PlGF levels were measured using enzyme linked immunosorbent assay (ELISA). Result: This study showed the level of maternal serum sFlt-1 was 7522.95 pg/mL and the level of maternal serum PlGF was 222.25 pg/mL. There was a difference between sflt-1, PlGF, and the sflt-1/PlGF ratio (p=0.00; p=0.00; p=0.00) in early and late onset of PE where at early onset PE was found higher sflt-1 and late-onset PE had lower PlGF and higher sflt-1/PlGF ratio. Conclusion: There are differences in sFlt-1, PlGF, and sFlt-1/PlGF in early and late onset PE, as higher sflt-1 is found in early onset preeclampsia, while lower PlGF and higher sflt-1/PlGF ratio are found in late onset preeclampsia.Keywords: early onset, late onset, preeclampsia, maternal angiogenesis factor, Flt-1, PlGF